AWARENESS AND PERCEIVED BENEFITS OF KWARA STATE HEALTH INSURANCE SCHEME AMONG RESIDENTS OF ADEWOLE ILORIN WEST LGA KWARA STATE (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
This study assesses the assessed awareness and perceived benefits of Kwara state insurance scheme among residents of Adewole in Ilorin West LGA Kwara state. The study used a descriptive cross-sectional study design. Residents of the Adewole community, which is part of the Ilorin West Local Government Area, participated in this study. For the study on perceptions of Kwara State's benefits and awareness, a multi-stage sampling technique was employed. Adewole, Ilorin West LGA, Kwara state people are covered by a health insurance program. In the first stage, five villages were chosen at random from the total number of villages in Ilorin West. Additionally, households in the streets of the chosen villages were chosen through systematic random sampling. To guarantee that adults were recruited for the study, respondents were chosen by a purposive method. The data obtained from the study were analyzed using SPSS version 21 (Statistical Package for the Social Sciences). The use of descriptive statistics was made, and frequency tables and percentages were used to present the data. To assess the degree of association between chosen variables at p